Greek kindergarten children’s motivation for reading - Chlapana, Elissavet; Tafa, Eufimia; Linardakis, Michalis (Preschool and Primary Education, 2023)
The aim of the present study was to investigate Greek kindergarten children’s reading motivation and their gender differences in reading motivation during kindergarten attendance. The sample of the present study consisted of 100 kindergarten children enrolled in public schools in Crete. The “Me and my reading profile” (MMRP) reading motivation tool was used. The MMRP was adjusted to Greek and was given to sample children in the beginning and at the end of the school year. Data analysis conducted with exploratory and confirmatory factor analysis revealed a 5-scale factorial structure in children’s reading motivation. Results showed that kindergarteners enhanced their reading motivation throughout the school year in the 3 out of the 5 extracted factors, while significant differences were found in the degree of reading motivation improvement between boys and girls. The results are important because they present data related to children’s reading motivation development at the first stages of literacy acquisition and are useful for making specific suggestions about educational practice and policy in Greece.